Structure of evaporating single- and multicomponent fuel sprays for 2nd generation gasoline direct injection - Zigan, Lars; Schmitz, Ingo; Flügel, Alexandre; Wensing, Michael; Leipertz, Alfred (Fuel, 2011)
In the present paper the effect of fuel properties on spray formation and evaporation was investigated for a hollow-cone spray of a piezoelectric injector for Direct Injection Spark Ignition (DISI) engines. Late injection timing in a high-pressure atmosphere (1.5 MPa, 200 °C) was simulated in an injection chamber. Liquid and vapor phase structure of the hollow-cone spray were studied with 2D-Mie scattering, laser-induced fluorescence (LIF) as well as phase-Doppler anemometry (PDA). The spray structure was investigated for several alkanes with high and low volatility (n-hexane, n-heptane, iso-octane, n-decane) and a three-component mixture of the n-alkanes with similar fuel properties like a multicomponent gasoline fuel. It is found that the rapid evaporation of high volatility fuels can lead to spray destabilization, whereas low volatility single-component fuels overestimate radial spray propagation and vortex formation. For iso-octane the droplet size distribution is shifted to smaller droplets and the spray appeared to be less dense compared to n-heptane despite almost identical boiling behavior. However, the much higher viscosity of iso-octane determines the internal nozzle flow which results in a reduced injected fuel mass and changed atomization. A well defined three-component fuel models the global spray characteristics as well as the droplet size, droplet momentum distribution and evaporation behavior of the used multicomponent gasoline fuel very precisely. Small amounts of low volatility fractions delay the droplet evaporation and support the overall spray stability also for multicomponent mixtures. This leads to an increased spray width as well as larger droplet sizes and momenta. The evaporation characteristic of multicomponent fuels at increased ambient pressure is complex. At the studied injection conditions it is situated between the two limiting cases of distillation-like behavior and coevaporation of the components. Moreover, the results in comparison with theoretical estimations indicate a demixing of light and heavy boiling fractions in the three-component and multicomponent fuel under conditions which are typical for DISI strategies with late injection. © 2010 Elsevier Ltd. All rights reserved.
Created from Fastlane, Scopus look-up
Keywords: Atomization; Evaporation; Gasoline direct injection; Multicomponent fuels; Spray structure